The civilizational discourse concept according to Islamic and western perspectives: a comparative analysis - Mohamad Zaidin, Mat@Mohamad; Abdillah Hisham, Ab. Wahab; Ahmad Fauzi, Hassan (Penerbit Universiti Sultan Zainal Abidin, 2020)
Civilization discourse is an alternative to the clash of civilizations. It is a form of positive interaction between civilizations that can lead to peace, cooperation and progress for all parties. Hence, surely there are similarities or differences in the perspective of all parties concerned about this concept because of differences in the fundamentals and sources held by these parties. This study intended to determine the extent of these similarities and differences in the civilization discourse concept according to Islamic and Western perspectives. This study was qualitative in nature and applied the content analysis approach. Findings show that similarity in values found in this concept was consistent with human instinct and humanistic values. However, differences that exists are from the source of this concept, which according to the Islamic perspective, involves certain laws because it is based on divine revelation from Allah SWT, while the West sees it solely from ethical and humanistic aspects.